THE EFFECT OF TIDAL WATER ON WELL WATER QUALITY IN NORTHERN COAST ROAD: A Case Study In Ulujami Sub-District Pemalang Regency - Asyifa, Adwiyah; Wibowo, Pebri Ari (University of Technology Yogyakarta, 2020)
Ulujami Sub-district is one of the sub-districts in Pemalang Regency, Central Java. Ulujami Sub-district is around 2305 ha, covering 18 urban villages. The 18 villages are: Ambowetan, Blendung, Botekan, Bumirejo, Kaliprau, Kertosari, Ketapang, Limbangan, Mojo, Padek, Pagergunung, Pamutih, Pesantren, Rowosari, Samong, Sukorejo, Tasikrejo, Wiyorowetan. It’s a densely populated region. Some urban villages are located at the northern coastline of Java and along rivers, and are often hit by tidal floods. Therefore, a study on the effect of tidal water on the quality of well water at the coastline of Pemalang Regency, specifically Ulujami Sub-district, is necessary. The data required by the present study were administrative map and well water quality parameters from the Decision of the Minister of Health No.416/MenKes/Per/XI/2010. The instruments were GPS, stationary, and Water Quality Checker. The well water sampling used stratified random sampling technique. The analysis included quality test of well water in tidal flood areas. The research result showed that in general the well water quality in Ulujami Sub-district was unqualified for daily needs. However, some locations near the coast showed high salt content, so well water wasn’t recommended for drinking, especially water from dug well. The well condition in Ulujami Sub-district is generally not fit for use. Of 36 tested well water in Ulujami Sub- district, 88.89% of the wells had odorless water, and 11.11% had slightly odored water, 11.1% had salty water, 3.89% had slightly salty water, and 75% had non-salty water, 44.44% had clear water, 33.33% had slightly cloudy water, and 22.22% had cloudy water.